Direct Trace Element Determination in Oil and Gas Produced Waters with Inductively Coupled Plasma‐Optical Emission Spectrometry: Advantages of High‐Salinity Tolerance. Issue 2 (9th April 2020) - Jubb, Aaron M.; Engle, Mark A.; Chenault, Jessica M.; Blondes, Madalyn S.; Danforth, Cloelle G.; Doolan, Colin; Gallegos, Tanya J.; Mueller, Dan; Shelton, Jenna L.
Abstract : Waters co‐produced during petroleum extraction are the largest waste streams from oil and gas development. Reuse or disposal of these waters is difficult due to their high salinities and the sheer volumes generated. Produced waters (PWs) may also contain valuable mineral commodities. While an understanding of produced water trace element composition is required for evaluating the associated resource and waste potential of these materials, measuring trace elements in brines is challenging due to the dilution requirements of typical methods. Alternatively, inductively coupled plasma‐optical emission spectrometry (ICP‐OES) has shown promise as being capable of direct measurements of trace elements within PWs with minimal dilution. Here, we evaluate direct ICP‐OES trace element quantification in PWs for seventeen trace elements (As, Al, Ba, Be, Cd, Cr, Co, Cu, Hg, Mo, Ni, Pb, Rb, Sb, U, V and Zn) within fifteen PWs from five U.S. continuous reservoirs. The total analytical uncertainties associated with the trace element levels determined using ICP‐OES were estimated to be better than ± 30% (2 s ) except for Rb, which could not be determined due to ionisation interferences. The ICP‐OES results are compared with trace element levels determined using inductively coupled plasma‐mass spectrometry from the same samples. Our results demonstrate the potential for direct analysis of high‐salinity waters using ICP‐OES with minimal dilution and provide trace element concentrations in waters from several important U.S. petroleum‐generating reservoirs where available data are sparse. Key Points: An ICP-OES method is described for the detection and quantification of 17 trace elements within high-salinity produced waters from several U.S. unconventional petroleum-generating reservoirs. ICP-OES results are compared with ICP-MS analyses of the same samples. Produced water trace element concentrations are provided for reservoirs where there is currently little or no available data.